2013
DOI: 10.1002/pssb.201248567
|View full text |Cite
|
Sign up to set email alerts
|

Role of defects in enhancing room temperature ferromagnetism of Mn doped ZnO nanoparticles

Abstract: The soft chemical route was used in the synthesis of undoped and 5% Mn doped ZnO nanocrystalline powders. XRD, TEM, TGA/DTA, FTIR, and superconducting quantum interference device techniques were used to study the structural, nano/microstructural, thermal decomposition and metastability aspects as a function of calcination temperatures (400–1100 °C) and magnetic properties. The evolution of the major wurtzite phase (ZnO) and minor non‐stoichiometric nanocrystalline defect cubic spinel phase (ZnMnO3–δ) at variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Though the room temperature ferromagnetic ordering in ZnO has controversial origins, intrinsic defects and magnetic impurities and/or impurity phases are the primary causes. Hence, the type of point defect which is important to induce the ferromagnetism in the prepared NPs is studied well through PL and EPR spectroscopic analysis and confirmed as zinc vacancies. Analogous to the present case, a few research findings are reviewed in the literature. , Particularly, in Mn-doped ZnO, first-principles calculations and X-ray absorption fluorescence spectroscopy (XAFS) studies revealed the existence of singly ionized zinc vacancies which favor the RTFM .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Though the room temperature ferromagnetic ordering in ZnO has controversial origins, intrinsic defects and magnetic impurities and/or impurity phases are the primary causes. Hence, the type of point defect which is important to induce the ferromagnetism in the prepared NPs is studied well through PL and EPR spectroscopic analysis and confirmed as zinc vacancies. Analogous to the present case, a few research findings are reviewed in the literature. , Particularly, in Mn-doped ZnO, first-principles calculations and X-ray absorption fluorescence spectroscopy (XAFS) studies revealed the existence of singly ionized zinc vacancies which favor the RTFM .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recent studies have shown that applying high field to Mn doped ZnO system would be a crucial factor in order to obtain RTFM behavior and the connection between nanocrystalline secondary phase and magnetism has been thought as and important factor for the RTFM. In our earlier publication, separately synthesized non-stoichiometic DCS-ZnMnO 3- exhibited RTFM with M s = 0.0035 emu g -1 and H c = 22 Oe but with the application of high field as 5 kOe [21].…”
Section: Resultsmentioning
confidence: 92%
“…The DC magnetization data for the sample with n = 0.30 collected at 4.5 K and 40 K is presented in Figure 5. The results of the DC magnetization measurements indicated the presence of a hysteresis loop at low temperatures, with a coercive field of approximately 0.2 T at 4.5 K. On the other hand, previous studies have reported superparamagnetic, ferrima netic, and spin-glass behavior of ZnMnO3 nanoparticles [57][58][59]. We attributed the o served magnetic behavior of the calcined ZnO(MnO) samples to the presence of ZnMn nanocrystals, exhibiting superparamagnetic behavior above a blocking temperature ( below 10 K) [36].…”
Section: Magnetic Studiesmentioning
confidence: 78%
“…We attributed the o served magnetic behavior of the calcined ZnO(MnO) samples to the presence of ZnMn nanocrystals, exhibiting superparamagnetic behavior above a blocking temperature ( below 10 K) [36]. Below the blocking temperature, we observed very narrow hystere loops in DC magnetization with very low coercivity values (HC~0.04 T at 4.5 K) for t calcined ZnMnO3 phase [58]. In contrast, the DC magnetization measurements in t work showed much higher coercivity field values, as seen in Figure 5.…”
Section: Magnetic Studiesmentioning
confidence: 79%